The Empowerment of Youth Red Cross of SMK 2 PGRI Malang City as Voluntary Blood Donor Volunteers - Sudiwati, Ni Luh Putu Eka; Panggayuh, Ardi; Ariani, Nia Lukita (Sahabat Publikasi Kuu, 2025)
The availability of blood is highly dependent on the willingness and awareness of the community to donate their blood voluntarily and regularly. The main target of donor recruitment is to obtain the amount of blood according to needs, which is focused on low-risk voluntary blood donors. Thus, efforts need to be made to increase young blood donors by conducting regular socialization about the benefits of blood donation in high schools, including related materials about blood donation and the Red Cross in Palang Merah Remaja (PMR) activities. Through this community service, it is expected that a more effective blood service network will be formed between the community, health centers, health services, hospitals, and blood donor unit. The stages used in this community service are preparation, implementation, and evaluation. We conducted a health education through visual media and simulation for students and members of PMR at SMK 2 PGRI Malang. The results of community service indicate that there is an increase in students' understanding of donor selection requirements. The simulation of basic life support session for the PMR members of SMK 2 PGRI Malang, was conducted without any difficulty. Students were quite enthusiastic about participating in the basic life support simulation.